KEPUASAN KONSUMEN PADA MENU BEST SELLER (NASI GORENG PANGERAN) DI RESTORAN HOTEL PANGERAN BEACH PADANG - Putri, Saima; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine Costumer Satisfaction with the Best Seller Menu (Nasi Goreng Pangeran) at the Pangeran Beach Hotel Padang, including 5 sub-variables (1) Product Quality, (2) Service Quality, (3) Emotional Factors, (4) Price, (5) Cost. This research uses quantitative methods using a Likert scale and the data collection techniques used are observation, questionnaires and documentation. The research population was guests who visited and ordered the Nasi Goreng Pangeran menu at the Hotel Pangeran Beach Padang restaurant and the research sample size was 100 people. Based on the research results, it can be concluded that consumers who order and eat Prince fried rice at the Pangeran Beach Padang Hotel restaurant can be said to be very satisfied with a total score of 7341 where the overall score range of 7150-8800 falls into the